Aspects IRM du rachis cervical des plongeurs pratiquant le plongeon en compétition - Jan, J.; Le Pourcelet-Talvard, C.; Lasbleiz, J. (Science & Sports, 2017)
Aims: The aim of this study was to evaluate effect of the dive (high performance practice) on the cervical spine, to define a classification of MRI findings and to assist in giving informed advice on the dive practice. Methods: The study involved 23 high performance divers, 12 women and 11 men (mean age 17) on who were performed cervical spine MRI. A MRI findings classification has been made to give practice authorisation of the dive with or without restriction. Results: Thirty-nine percent of divers had cervical MRI abnormalities especially on C4-C5 and C5-C6 levels. Those abnormalities led to high diving interdiction for 13% of divers. Fifty-three percent of divers with MRI abnormalities have practiced gymnastics before the dive. Our study showed the interest of cervical spine MRI in giving informed advice on the dive practice and other sports with high cervical trauma risk for example gymnastics.